SELF-Adaptability SOFTWARE FOR IMAGE ANALYSIS - A. M. Nedzved; V. V. Starovoytov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The method for development of intelligent software for image analysis is described. It is based on control shell of scripts generating that are controlled by an intelligent agent in software. The method is based on a combination of features of dynamic libraries and interpreter with a lot of functions for image processing.